A supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst, preparation method and application thereof

The Mn-M-O composite metal oxide is loaded on hydrotalcite by loading layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst, which solves the problems of low efficiency and poor stability of ozone and VOCs coordinate control in the prior art, and achieves efficient O3 decomposition and VOCs degradation effects.

CN117358224BActive Publication Date: 2025-04-29NANJING UNIV OF INFORMATION SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311489307.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2025-04-29
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

The prior art has problems of low efficiency, poor stability and high cost in the coordinated control of ozone and volatile organic compounds (VOCs), especially in the case of difficult to effectively decompose high concentrations of O3 and difficult degradation VOCs such as toluene under normal temperature conditions.

Method used

A supported layered Mn-M(Ce,Cr,Fe)-O hydrotalcite catalyst is used. This catalyst improves the adsorption capacity and oxidative degradation capacity of the catalyst by supporting the Mn-M-O composite metal oxide on hydrotalcite.

Benefits of technology

Under normal temperature conditions, the catalyst can efficiently decompose O3, with an O3 decomposition efficiency greater than 95%, and efficiently oxidize and degrade low-concentration formaldehyde in indoor environments, with a formaldehyde removal rate as high as 93.6% or above, and has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117358224B_ABST
    Figure CN117358224B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical fields of air pollution control and catalytic materials, and particularly relates to a supported layered Mn-M(Ce,Cr,Fe)-O hydrotalcite catalyst, a preparation method and an application thereof; the preparation method is as follows: MgCl2·6H2O, Al(NO3)3·9H2O, Mn(NO3)2 and Cr(NO3)3·9H2O are successively dissolved in deionized water to obtain solution A, then a Na2CO3 solution and a NaOH solution are mixed to obtain solution B, solution B is dropped into solution A to adjust the pH of solution A to 10 to obtain solution C, solution C is centrifuged, washed and dried to obtain layered MgMnAlCr-LDH hydrotalcite; Mn(NO3)2 is dissolved in deionized water to obtain solution D, an active agent is added to solution D and stirred until the active agent is completely dissolved in solution D to obtain solution E, citric acid is added to solution E and stirred until citric acid is completely dissolved to obtain solution F, solution F is steamed until it becomes gel-like, layered MgMnAlCr-LDH hydrotalcite is added to the gel-like F and stirred to obtain gel-like G, and the gel-like G is dried, calcined and ground to obtain a catalyst of supported layered Mn-M-O and hydrotalcite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of air pollution control and catalytic material technology, and in particular to a supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst, a preparation method and application thereof. Background Art

[0002] Ozone (O3) and fine particulate matter (PM 2.5 ) are the two main pollutants that currently plague my country's atmospheric environmental quality. Due to the low atmospheric environmental capacity in winter, it is very easy to induce PM 2.5 Heavy pollution weather with excessive pollution; Summer ground-level ozone, as an emerging pollutant, seriously threatens human health. 2.5 Atmospheric environmental problems represented by the two major pollutants of O3 and ozone are becoming increasingly severe. A large number of studies have confirmed that VOCs are important precursors to fine particulate matter, organic secondary aerosols and near-ground ozone. The coordinated control of O3 and VOCs is of great significance to solving the current air pollution.

[0003] Currently reported ozone removal methods include liquid absorption, thermal decomposition, activated carbon adsorption and catalytic decomposition. Among them, the liquid absorption method is costly and the waste liquid is difficult to handle, the thermal decomposition method has high energy consumption, and the activated carbon adsorption method is easy to saturate and difficult to regenerate. The ozone catalytic decomposition method can achieve efficient decomposition of ozone at room temperature without any secondary pollution. It is the ozone removal technology with the most research value and application potential. The key to this technology lies in the preparation of efficient catalytic materials.

[0004] Volatile organic compounds (VOCs) are the most common major indoor environmental pollutants, and formaldehyde (HCHO) is one of the typical pollutants that causes numerous health problems for humans. When the human body is in an environment with a formaldehyde concentration greater than 0.1 mg / m3, it may cause damage to the respiratory system, and long-term exposure will cause damage to other organs of the human body. Formaldehyde has been listed as a Class I carcinogen, which seriously threatens human health. At present, there are physical, biological and chemical methods to prevent and control indoor formaldehyde pollution. Physical methods include natural ventilation and adsorption, biological methods include plant ecological purification and microbial degradation, and chemical methods include plasma method and catalytic oxidation technology. The physical method has low cost and high efficiency, but it cannot completely solve the formaldehyde pollution problem and may also cause secondary pollution; the biological method is green and environmentally friendly, has low treatment cost and no secondary pollution, but is limited by environmental temperature / humidity, strain selection and other conditions, and has low efficiency; although plasma technology is less affected by the environment, it requires external conditions, has high energy consumption and poor safety; catalytic oxidation technology has been proven to be an effective formaldehyde removal method, which specifically includes thermal catalysis, photocatalysis, room temperature catalysis, ozone purification, etc., all of which have unique advantages. Among them, room temperature catalytic oxidation technology has the advantages of simple operation, low energy consumption, no secondary pollution and high purification efficiency, and has attracted widespread attention. It has important application research value in achieving the removal of low-concentration gaseous formaldehyde in indoor environments, and the preparation of efficient, stable and inexpensive catalysts is the core of room temperature catalytic oxidation technology.

[0005] At present, room temperature catalytic oxidation catalysts can be divided into two categories: one is precious metal catalysts; the other is transition metal oxide catalysts. Precious metals such as Pt, Pd, Au and Ag are usually prepared with high specific surface area carriers such as TiO2, Al2O3, SiO2, Co3O4, CeO2, etc. They have high activity and excellent degradation performance, but precious metal resources are scarce and expensive, which limits their wide range. Transition metal oxides have the potential to replace precious metals due to their rich resources, high oxidation activity and good stability. Studies have found that transition metal manganese oxides (MnO x ) has excellent performance in formaldehyde degradation, strong oxidation ability, high CO2 selectivity, and adjustable crystal form, valence state, and morphology, and has broad application prospects. The researchers prepared graphene-MnO2 composite nanomaterials by hydrothermal method. Compared with the single metal catalyst MnO2, the temperature required for the composite catalyst to completely catalyze formaldehyde was reduced by 75°C, the catalytic performance was improved, and graphene enhanced the Mn 3+ and Mn 4+The charge transfer between the two species produces abundant hydroxyl radicals on the catalyst surface, which improves the degradation activity of formate, an intermediate product of formaldehyde catalytic oxidation. The researchers also prepared doped MnO2 by redox method and cerium modification. The study found that with the increase of Ce doping amount, the crystallinity of MnO2 decreased and the specific surface area of ​​the catalyst increased. When the molar ratio of cerium to manganese in Ce-MnO2 reached 1:10, the catalyst had stable catalytic performance at room temperature, and low-concentration formaldehyde could be completely oxidized to CO2 and H2O at 100°C. This is because Ce-doped MnO2 has more surface adsorbed oxygen, which reduces the grain boundary spacing between CeO2 nanoclusters and MnO2, and improves the redox ability and migration rate of surface oxygen and lattice oxygen. The researchers also investigated the effects of α-MnO2 crystal form, morphology and high-valent metal doping modification on its ozone catalytic performance, and tested the ozone catalytic performance of α-MnO2, β-MnO2 and γ-MnO2, among which α-MnO2 showed the best ozone catalytic activity. Studies have shown that α-MnO2 has a larger specific surface area and richer Mn 3+ In situ Raman observations revealed the formation of peroxide intermediates during ozone catalytic decomposition, and the peroxides on α-MnO2 were most easily desorbed. Based on these results, an ozone decomposition mechanism with oxygen defects as active sites was proposed.

[0006] Domestic and foreign scholars have also conducted extensive and in-depth research in this field, focusing mainly on the influence of material chemical composition on O3 decomposition and room-temperature catalytic oxidation of VOCs, such as MnO x 、Co3O4、MnO x -CeO2, Cu-Mn-Ce-O, Co-Ce-O, Ce-La-O, Mn-Ce-La-O and other transition metal oxides have been systematically and deeply studied for the catalytic oxidation of VOCs and O3 decomposition at room temperature. The study found that the activity of composite oxides is significantly higher than that of single-component oxides, and when the active components are pretreated to form solid solutions or composite oxides, the catalytic activity can be further improved. However, common transition metal oxide catalysts still face huge challenges under room temperature conditions: (1) The adsorption capacity of the catalyst needs to be improved, especially for high-concentration VOCs and O3; (2) The oxidation and degradation ability of the catalyst needs to be improved, especially for difficult-to-degrade VOCs such as toluene; (3) The catalyst has problems such as reduced performance stability due to the adsorption of water vapor; Therefore, domestic and foreign scholars have conducted a lot of research on the search for efficient and stable catalytic oxidation of VOCs catalyst systems, considering combining transition metal oxides with different carriers to improve the catalyst's decomposition of O3 at room temperature and the oxidation and degradation of low-concentration VOCs indoors.

[0007] LDHs are clay materials with a brucite structure (Mg(OH)2) and anion exchange properties. These materials can generally be described by the formula [M 2+ 1-x M 3+ x (OH)2] b+ [An-] b / n mH2O means, where M 2+ and M 3+ are divalent and trivalent metal cations, respectively, and A is an interlayer anion, usually a carbonate. These oxides have the characteristics of mesoporous structure, acid-base dual functionality, thermal stability, adsorption, interlayer anion exchangeability, and high specific surface area. In recent decades, hydrotalcite-like materials have attracted widespread attention due to their wide applications in ion exchangers, adsorbents, catalysts, etc. Prepared hydrotalcite-like materials are rarely used as catalysts alone because they are located in carbonates and do not have active sites of the necessary strength. However, the hydroxyl groups on the surface of hydrotalcite-like materials can enhance the catalytic oxidation effect. Introducing active centers on the surface of hydrotalcite-like materials can effectively improve the efficiency of decomposing O3 and catalytic oxidation of VOCs at room temperature. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst, a preparation method and an application thereof.

[0009] The purpose of the present invention can be achieved through the following technical solutions:

[0010] A method for preparing a supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst, the preparation method comprising the following steps:

[0011] S1. Dissolve MgCl2·6H2O, Al(NO3)3·9H2O, Mn(NO3)2 and Cr(NO3)3·9H2O in deionized water in turn to obtain solution A, then mix Na2CO3 solution and NaOH solution to obtain solution B, slowly drip solution B into solution A to adjust the pH of solution A to 10 to obtain solution C, centrifuge, wash and dry solution C to obtain layered MgMnAlCr-LDH hydrotalcite;

[0012] S2. Dissolve Mn(NO3)2 in deionized water to obtain solution D, add an activator to solution D and stir to completely dissolve the activator in solution D to obtain solution E, add citric acid to solution E and stir to completely dissolve the citric acid to obtain solution F, boil solution F to make it gel-like, add layered MgMnAlCr-LDH hydrotalcite to gel F and stir to obtain gel G, dry, calcine and grind gel G to obtain a catalyst of supported layered Mn-MO and hydrotalcite.

[0013] Preferably, in step S1, the molar ratio of n(Mg) / n(Al) is 4:1 to 1:4, and the molar ratios of n(Mn) / n(Mg) and n(Cr) / n(Al) are both 1:4.

[0014] Preferably, in step S1, the volume ratio of the Na2CO3 solution to the NaOH solution is 1:1, the concentration of the Na2CO3 solution is 0.2 mol / L, and the concentration of the NaOH solution is 1 mol / L.

[0015] Preferably, deionized water is used for washing in step S1, the number of washing times is at least 3 times, and the drying temperature in step S1 is 80° C. to 100° C. for 10 h to 12 h.

[0016] Preferably, the active agent in step S2 is one or more of Ce(NO3)3·6H2O, Cr(NO3)3·9H2O or Fe(NO3)3·9H2O.

[0017] Preferably, in step S2, cooking is performed in a water bath at a cooking temperature of 75°C to 85°C.

[0018] Preferably, in step S2, the drying temperature is 80°C to 100°C, the time is 5h to 7h, and the calcination temperature is 200°C to 400°C, the time is 3h to 5h.

[0019] Preferably, the supported layered Mn-M(Ce, Cr, Fe)-O and hydrotalcite catalyst is prepared by the preparation method.

[0020] Preferably, the active components of the supported layered Mn-M(Ce, Cr, Fe)-O and hydrotalcite catalyst are one or more of Mn-Ce-O, Mn-Cr-O, Mn-Fe-O, Mn-Ce-Cr-O, Mn-Ce-Fe-O, Mn-Cr-Fe-O and Mn-Ce-Cr-Fe-O, wherein the n(Mn) / n(M) molar ratio is 6:1 to 2:1, the n(Ce) / n(Cr), n(Ce) / n(Fe) and n(Cr) / n(Fe) molar ratios are all 1:1, and the mass fraction of the Mn-MO mixed / composite metal oxide loading is 20%-40%.

[0021] Preferably, the supported layered Mn-M(Ce, Cr, Fe)-O and hydrotalcite catalyst is used in the preparation of ozone or volatile organic compound adsorption products.

[0022] Beneficial effects of the present invention:

[0023] The catalyst prepared by the present invention is mainly used for decomposition of O3 and oxidation degradation of low-concentration VOCs indoors, such as formaldehyde and toluene, at room temperature. The properties of the prepared catalyst are as follows:

[0024] (1) O3 decomposition: When the initial O3 concentration is 28 mg·m -3 , mass space velocity 600,000 mL·(g·h) -1 When the relative humidity RH = 50%, after 24 hours of continuous reaction, the O3 decomposition efficiency is greater than 95%;

[0025] (2) Oxidative degradation of formaldehyde: The catalyst (1.0 g, spread on a Φ = 90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), when the initial gaseous formaldehyde concentration is 1.0 mg / m 3 Its 48h formaldehyde removal rate is as high as 93.6% or above, which meets the national indoor air quality standard (GB / T18883-2002) and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0027] Figure 1 is a SEM image of a supported layered Mn-M(Ce, Cr, Fe)-O / hydrotalcite catalyst prepared by the present invention (Example 1);

[0028] Figure 2 The activity diagram of decomposing O3 by a supported layered Mn-M(Ce, Cr, Fe)-O / hydrotalcite catalyst prepared by the present invention (Examples 1, 2, 3, 4, 5 and 6);

[0029] Figure 3 The activity diagram of the supported layered Mn-M(Ce, Cr, Fe)-O / hydrotalcite catalyst prepared by the present invention for catalytic oxidation of formaldehyde at room temperature (Examples 1, 2, 3, 4, 5 and 6). DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment 1:

[0032] Step I: Preparation of layered MgMnAlCr-LDH hydrotalcite

[0033] 8.12g MgCl2·6H2O, 2.13g Al(NO3)3·9H2O, 2.32mL Mn(NO3)2 and 1.01g Cr(NO3)3·9H2O were dissolved in 100mL deionized water, recorded as solution A; 50mL, 0.2mol / LNa2CO3 solution and 50mL, 1mol / LNaOH solution were mixed, recorded as solution B; solution A was placed on a magnetic stirrer for continuous stirring, while solution B was slowly added thereto, and the pH of the solution was tested with an acidity meter until the pH of the solution reached 10, and the addition was stopped and stirring was continued for 3h. The above solution was then centrifuged and washed with deionized water 3 times, and the resulting hydrogel was placed in an oven at 80°C and dried for 12h to obtain Mn 2+ and Cr 3+ Co-doped layered MgAl-LDH hydrotalcite support, i.e., MgMnAlCr-LDH;

[0034] Step II: Preparation of a supported layered Mn-Ce-O / hydrotalcite catalyst

[0035] 9.28 mL Mn(NO3)2 and 4.34 g Ce(NO3)3·6H2O were respectively dissolved in 200 mL deionized water, stirred until completely dissolved, and 57.6 g citric acid was added and stirred until completely dissolved; the above solution was then placed in an 80°C water bath for steaming to form a sol, and 3 g of the above layered MgMnAlCr-LDH hydrotalcite powder was immersed in the sol, stirred appropriately, and allowed to stand until a gel was formed, dried at 80°C for 6 h, calcined at 400°C for 4 h, and ground to obtain a supported layered Mn-Ce-O / hydrotalcite catalyst, whose active component is a Mn-Ce-O mixed / composite metal oxide;

[0036] The prepared supported layered Mn-Ce-O / hydrotalcite catalyst was heated in a micro fixed bed quartz tube reactor at a mass space velocity of 600,000 mL·(g·h) -1 , relative humidity RH = 50%, the initial ozone concentration is adjusted by the ozone generator to 28 mg·m -3 When the reaction was continued for 24 h, the decomposition efficiency of O3 was maintained at 100%; the prepared supported layered Mn-Ce-O / hydrotalcite catalyst (1.0 g, spread on a Φ=90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), the initial gaseous formaldehyde concentration is 1.0 mg / m 3 The conversion efficiency of formaldehyde within 48 hours was 97.3%.

[0037] Embodiment 2:

[0038] Step I: Preparation of layered MgMnAlCr-LDH hydrotalcite

[0039] 8.12g MgCl2·6H2O, 8.52g Al(NO3)3·9H2O, 2.32mL Mn(NO3)2 and 4.00g Cr(NO3)3·9H2O were dissolved in 100mL deionized water, recorded as solution A; 50mL, 0.2mol / LNa2CO3 solution and 50mL, 1mol / LNaOH solution were mixed, recorded as solution B; solution A was placed on a magnetic stirrer for continuous stirring, while solution B was slowly added thereto, and the pH of the solution was tested with an acidity meter until the pH of the solution reached 10, and the addition was stopped and stirring was continued for 3h. The above solution was then centrifuged and washed with deionized water 3 times, and the resulting hydrogel was placed in an oven at 80°C and dried for 12h to obtain Mn 2+ and Cr 3+ Co-doped layered MgAl-LDH hydrotalcite support, i.e., MgMnAlCr-LDH;

[0040] Step II: Preparation of a supported layered Mn-Cr-O / hydrotalcite catalyst

[0041] 13.92 mL of Mn(NO3)2 and 4.00 g of Cr(NO3)3·9H2O were respectively dissolved in 200 mL of deionized water, stirred until completely dissolved, and 80.64 g of citric acid was added and stirred until completely dissolved; the above solution was then placed in an 80°C water bath and boiled to form a sol, and 5 g of the above layered MgMnAlCr-LDH hydrotalcite powder was immersed in the sol, stirred appropriately, and allowed to stand until a gel was formed, dried at 80°C for 6 h, calcined at 300°C for 4 h, and ground to obtain a supported layered Mn-Cr-O / hydrotalcite catalyst, whose active component is a Mn-Cr-O mixed / composite metal oxide;

[0042] The prepared supported layered Mn-Cr-O / hydrotalcite catalyst was heated in a micro fixed bed quartz tube reactor at a mass space velocity of 600,000 mL·(g·h) -1 , relative humidity RH = 50%, the initial ozone concentration is adjusted by the ozone generator to 28 mg·m -3 After 24 h of continuous reaction, the decomposition efficiency of O3 was maintained at 95%. The prepared supported layered Mn-Cr-O / hydrotalcite catalyst (1.0 g, spread on a Φ=90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), the initial gaseous formaldehyde concentration is 1.0 mg / m 3 The conversion efficiency of formaldehyde within 48 hours was 95.4%.

[0043] Embodiment 3:

[0044] Step I: Preparation of layered MgMnAlCr-LDH hydrotalcite

[0045] 2.03g MgCl2·6H2O, 8.52g Al(NO3)3·9H2O, 0.58mL Mn(NO3)2 and 4.00g Cr(NO3)3·9H2O were dissolved in 100mL deionized water, recorded as solution A; 50mL, 0.2mol / LNa2CO3 solution and 50mL, 1mol / LNaOH solution were mixed, recorded as solution B; solution A was placed on a magnetic stirrer for continuous stirring, while solution B was slowly added thereto, and the pH of the solution was tested with an acidity meter until the pH of the solution reached 10, and the addition was stopped and stirring was continued for 3h. The above solution was then centrifuged and washed with deionized water 3 times, and the resulting hydrogel was placed in an oven at 80°C and dried for 12h to obtain Mn 2+ and Cr 3+Co-doped layered MgAl-LDH hydrotalcite support, i.e., MgMnAlCr-LDH;

[0046] Step II: Preparation of a supported layered Mn-Fe-O / hydrotalcite catalyst

[0047] 4.65 mL of Mn(NO3)2 and 4.04 g of Fe(NO3)3·9H2O were respectively dissolved in 200 mL of deionized water, stirred until completely dissolved, and 34.56 g of citric acid was added and stirred until completely dissolved; the above solution was then placed in an 80°C water bath for steaming to form a sol, and 2.5 g of the above layered MgMnAlCr-LDH hydrotalcite powder was then immersed in the sol, stirred appropriately, and allowed to stand until a gel was formed, dried at 80°C for 6 h, calcined at 200°C for 4 h, and ground to obtain a supported layered Mn-Fe-O / hydrotalcite catalyst, whose active component is a Mn-Fe-O mixed / composite metal oxide;

[0048] The prepared supported layered Mn-Fe-O / hydrotalcite catalyst was heated in a micro fixed bed quartz tube reactor at a mass space velocity of 600,000 mL·(g·h) -1 , relative humidity RH = 50%, the initial ozone concentration is adjusted by the ozone generator to 28 mg·m -3 After 24 h of continuous reaction, the decomposition efficiency of O3 was maintained at 99%; the prepared supported layered Mn-Fe-O / hydrotalcite catalyst (1.0 g, spread on a Φ=90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), the initial gaseous formaldehyde concentration is 1.0 mg / m 3 The conversion efficiency of formaldehyde within 48 hours was 94.3%.

[0049] Embodiment 4:

[0050] Step I: Preparation of layered MgMnAlCr-LDH hydrotalcite

[0051] 8.12g MgCl2·6H2O, 2.13g Al(NO3)3·9H2O, 2.32mL Mn(NO3)2 and 1.00g Cr(NO3)3·9H2O were dissolved in 100mL deionized water, recorded as solution A; 50mL, 0.2mol / LNa2CO3 solution and 50mL, 1mol / LNaOH solution were mixed, recorded as solution B; solution A was placed on a magnetic stirrer for continuous stirring, while solution B was slowly added thereto, and the pH of the solution was tested with an acidity meter until the pH of the solution reached 10, and the addition was stopped and stirring was continued for 3h. The above solution was then centrifuged and washed with deionized water 3 times, and the resulting hydrogel was placed in an oven at 80°C and dried for 12h to obtain Mn 2+ and Cr 3+ Co-doped layered MgAl-LDH hydrotalcite support, i.e., MgMnAlCr-LDH;

[0052] Step II: Preparation of a supported layered Mn-Ce-Cr-O / hydrotalcite catalyst

[0053] 9.28 mL Mn(NO3)2, 2.17 g Ce(NO3)3·6H2O and 2.00 g Cr(NO3)3·9H2O were respectively dissolved in 200 mL deionized water, stirred until completely dissolved and 57.6 g citric acid was added and stirred until completely dissolved; the above solution was then placed in an 80°C water bath for steaming to form a sol, and 3 g of the above layered MgMnAlCr-LDH hydrotalcite powder was immersed in the sol, stirred appropriately, and allowed to stand until a gel was formed, dried at 80°C for 6 h and calcined at 400°C for 4 h, and ground to obtain a supported layered Mn-Ce-Cr-O / hydrotalcite catalyst, whose active component is a Mn-Ce-Cr-O mixed / composite metal oxide;

[0054] The prepared supported layered Mn-Ce-Cr-O / hydrotalcite catalyst was heated in a micro fixed bed quartz tube reactor at a mass space velocity of 600,000 mL·(g·h) -1 , relative humidity RH = 50%, the initial ozone concentration is adjusted by the ozone generator to 28 mg·m -3 After 24 h of continuous reaction, the decomposition efficiency of O3 was maintained at 97%. The prepared supported layered Mn-Ce-Cr-O / hydrotalcite catalyst (1.0 g, spread on a Φ=90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), the initial gaseous formaldehyde concentration is 1.0 mg / m 3 The conversion efficiency of formaldehyde within 48 hours was 93.6%.

[0055] Embodiment 5:

[0056] Step I: Preparation of layered MgMnAlCr-LDH hydrotalcite

[0057] 8.12g MgCl2·6H2O, 8.52g Al(NO3)3·9H2O, 2.32mL Mn(NO3)2 and 4.00g Cr(NO3)3·9H2O were dissolved in 100mL deionized water, recorded as solution A; 50mL, 0.2mol / LNa2CO3 solution and 50mL, 1mol / LNaOH solution were mixed, recorded as solution B; solution A was placed on a magnetic stirrer for continuous stirring, while solution B was slowly added thereto, and the pH of the solution was tested with an acidity meter until the pH of the solution reached 10, and the addition was stopped and stirring was continued for 3h. The above solution was then centrifuged and washed with deionized water 3 times, and the resulting hydrogel was placed in an oven at 80°C and dried for 12h to obtain Mn 2+ and Cr 3+ Co-doped layered MgAl-LDH hydrotalcite support, i.e., MgMnAlCr-LDH;

[0058] Step II: Preparation of a supported layered Mn-Ce-Fe-O / hydrotalcite catalyst

[0059] 13.92 mL of Mn(NO3)2, 2.17 g of Ce(NO3)3·6H2O and 2.02 g of Fe(NO3)3·9H2O were respectively dissolved in 200 mL of deionized water, stirred until completely dissolved, and 80.64 g of citric acid was added and stirred until completely dissolved; the above solution was then placed in an 80°C water bath for steaming to form a sol, and 5 g of the above layered MgMnAlCr-LDH hydrotalcite powder was immersed in the sol, stirred appropriately, and allowed to stand until a gel was formed, dried at 80°C for 6 h and calcined at 300°C for 4 h, and ground to obtain a supported layered Mn-Ce-Fe-O / hydrotalcite catalyst, whose active component is a Mn-Ce-Fe-O mixed / composite metal oxide;

[0060] The prepared supported layered Mn-Ce-Fe-O / hydrotalcite catalyst was heated in a micro-fixed bed quartz tube reactor at a mass space velocity of 600,000 mL·(g·h) -1 , relative humidity RH = 50%, the initial ozone concentration is adjusted by the ozone generator to 28 mg·m -3 After 24 h of continuous reaction, the decomposition efficiency of O3 was maintained at 96%. The prepared supported layered Mn-Ce-Fe-O / hydrotalcite catalyst (1.0 g, spread on a Φ=90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), the initial gaseous formaldehyde concentration is 1.0 mg / m 3The conversion efficiency of formaldehyde within 48 hours was 95.5%.

[0061] Embodiment 6:

[0062] Step I: Preparation of layered MgMnAlCr-LDH hydrotalcite

[0063] 2.03g MgCl2·6H2O, 8.52g Al(NO3)3·9H2O, 0.58mL Mn(NO3)2 and 4.00g Cr(NO3)3·9H2O were dissolved in 100mL deionized water, recorded as solution A; 50mL, 0.2mol / LNa2CO3 solution and 50mL, 1mol / LNaOH solution were mixed, recorded as solution B; solution A was placed on a magnetic stirrer for continuous stirring, while solution B was slowly added thereto, and the pH of the solution was tested with an acidity meter until the pH of the solution reached 10, and the addition was stopped and stirring was continued for 3h. The above solution was then centrifuged and washed with deionized water 3 times, and the resulting hydrogel was placed in an oven at 80°C and dried for 12h to obtain Mn 2+ and Cr 3+ Co-doped layered MgAl-LDH hydrotalcite support, i.e., MgMnAlCr-LDH;

[0064] Step II: Preparation of a supported layered Mn-Cr-Fe-O / hydrotalcite catalyst

[0065] 4.65 mL Mn(NO3)2, 2.02 g Fe(NO3)3·9H2O and 2.00 g Cr(NO3)3·9H2O were respectively dissolved in 200 mL deionized water, stirred until completely dissolved, and 34.56 g citric acid was added and stirred until completely dissolved; the above solution was then placed in an 80°C water bath for steaming to form a sol, and 5 g of the above layered MgMnAlCr-LDH hydrotalcite powder was immersed in the sol, stirred appropriately, and allowed to stand until a gel was formed, dried at 80°C for 6 h and calcined at 200°C for 4 h, and ground to obtain a supported layered Mn-Cr-Fe-O / hydrotalcite catalyst, whose active component is a Mn-Cr-Fe-O mixed / composite metal oxide;

[0066] The prepared supported layered Mn-Cr-Fe-O / hydrotalcite catalyst was heated in a micro fixed bed quartz tube reactor at a mass space velocity of 600,000 mL·(g·h) -1 , relative humidity RH = 50%, the initial ozone concentration is adjusted by the ozone generator to 28 mg·m -3After 24 h of continuous reaction, the decomposition efficiency of O3 was maintained at 95%. The prepared supported layered Mn-Cr-Fe-O / hydrotalcite catalyst (1.0 g, spread on a Φ=90 mm culture dish) was placed in a glass reactor (0.125 m 3 ), the initial gaseous formaldehyde concentration is 1.0 mg / m 3 The conversion efficiency of formaldehyde within 48 hours was 94.7%.

[0067] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0068] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst, characterized in that: The preparation method comprises the following steps: S1. Dissolve MgCl2·6H2O, Al(NO3)3·9H2O, Mn(NO3)2 and Cr(NO3)3·9H2O in deionized water in turn to obtain solution A, then mix Na2CO3 solution and NaOH solution to obtain solution B, slowly drip solution B into solution A to adjust the pH of solution A to 10 to obtain solution C, centrifuge, wash and dry solution C to obtain layered MgMnAlCr-LDH hydrotalcite; S2. Dissolve Mn(NO3)2 in deionized water to obtain solution D, add an activator to solution D and stir to completely dissolve the activator in solution D to obtain solution E, add citric acid to solution E and stir to completely dissolve the citric acid to obtain solution F, boil solution F to make it gel-like, add layered MgMnAlCr-LDH hydrotalcite to gel F and stir to obtain gel G, dry, calcine and grind gel G to obtain a catalyst of supported layered Mn-MO and hydrotalcite.

2. The preparation method according to claim 1, characterized in that: The molar concentration of MgCl2·6H2O in step S1 is 0.625-1 mol / L, wherein the molar ratio of n(Mg) / n(Al) is 4:1-1:4, and the molar ratios of n(Mn) / n(Mg) and n(Cr) / n(Al) are both 1:

4.

3. The preparation method according to claim 2, characterized in that: In step S1, the volume ratio of the Na2CO3 solution to the NaOH solution is 1:1, the concentration of the Na2CO3 solution is 0.2 mol / L, and the concentration of the NaOH solution is 1 mol / L.

4. The preparation method according to claim 1, characterized in that: Deionized water is used for washing in step S1, and the number of washing times is at least 3 times. The drying temperature in step S1 is 80° C. to 100° C. for 10 h to 12 h.

5. The preparation method according to claim 1, characterized in that: In step S2, the active agent is one or more of Ce(NO3)3·6H2O, Cr(NO3)3·9H2O or Fe(NO3)3·9H2O.

6. The preparation method according to claim 1, characterized in that: In step S2, cooking is performed in a water bath at a temperature of 75°C to 85°C.

7. The preparation method according to claim 1, characterized in that: In step S2, the drying temperature is 80°C to 100°C, the time is 5h to 7h, and the calcination temperature is 200°C to 400°C, the time is 3h to 5h.

8. A supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. A supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst according to claim 8, characterized in that: The active components of the catalyst are one or more of Mn-Ce-O, Mn-Cr-O, Mn-Fe-O, Mn-Ce-Cr-O, Mn-Ce-Fe-O, Mn-Cr-Fe-O and Mn-Ce-Cr-Fe-O, wherein the molar ratio of n(Mn) / n(M) is 6:1-2:1, the molar ratios of n(Ce) / n(Cr), n(Ce) / n(Fe) and n(Cr) / n(Fe) are all 1:1, and the mass fraction of the Mn-MO mixed / composite metal oxide loading is 20%-40%.

10. Use of the supported layered Mn-M(Ce, Cr, Fe)-O hydrotalcite catalyst as claimed in claim 8 in preparing products for adsorbing ozone or volatile organic compounds.

Citation Information

Patent Citations

  • M-MnOx-CeO2 catalyst and application thereof

    CN109107567A

  • Catalyst for trapping VOCs and catalyzing degradation of VOCs, as well as preparation method and application of catalyst

    CN110653004A